PENGARUH KOMPENSASI FINANSIAL TERHADAP KINERJA DAN LOYALITAS DEWAN GURU DI SMA SUNAN AMPEL PUNGGUR - Fredi, Fredi Irawan; Sakun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the extent to which the financial compensation (honorarium) received by teachers at Sunan Ampel Punggur High School affects their performance and loyalty. The issue of teacher honorariums, often perceived as low, is a major concern, given their potential impact on work motivation and professional dedication. This study will employ a quantitative approach with a survey method, involving all teachers at Sunan Ampel Punggur High School as respondents. Data will be collected through a questionnaire designed to measure teachers' perceptions of the adequacy of their honorariums, their level of performance, and their level of loyalty to the institution. Data analysis will use regression techniques to test the causal relationship between financial compensation, performance, and loyalty. The results of this study are expected to provide a deeper understanding of the implications of financial compensation on important aspects of human resource management in educational settings. These findings are also expected to provide input for school management and relevant policymakers in formulating strategies to improve teacher welfare to support the achievement of optimal educational goals.